2018
DOI: 10.1002/smll.201801219
|View full text |Cite
|
Sign up to set email alerts
|

Protein Corona Mediated Uptake and Cytotoxicity of Silver Nanoparticles in Mouse Embryonic Fibroblast

Abstract: Medical applications of nanoparticles (NPs) require understanding of their interactions with living systems in order to control their physiological response, such as cellular uptake and cytotoxicity. When NPs are exposed to biological fluids, the adsorption of extracellular proteins on the surface of NPs, creating the so-called protein corona, can critically affect their interactions with cells. Here, the effect of surface coating of silver nanoparticles (AgNPs) on the adsorption of serum proteins (SPs) and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
75
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 56 publications
10
75
0
3
Order By: Relevance
“…Miclaus et al addressed that the weakly attached protein reduce nanocrystal formation in a serum-concentration-dependent manner, the strongly attached corona act as a site for sulphidation which decreases the toxicity of AgNPs [43]. On the other hand, Barbalinardo inferred that absorption of serum protein to AgNPs surface is essential for internalization and toxicity to cell [44]. Protein corona affects not only the pharmacokinetics of AgNPs in experimental animals but also the antibacterial efficiency in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Miclaus et al addressed that the weakly attached protein reduce nanocrystal formation in a serum-concentration-dependent manner, the strongly attached corona act as a site for sulphidation which decreases the toxicity of AgNPs [43]. On the other hand, Barbalinardo inferred that absorption of serum protein to AgNPs surface is essential for internalization and toxicity to cell [44]. Protein corona affects not only the pharmacokinetics of AgNPs in experimental animals but also the antibacterial efficiency in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The role of AgNP surface coatings in toxicity and cellular response has received significant attention. [3,[26][27][28][29][30][31] In our dataset, a comparison of DEGs across cells treated with bPEIcoated or CIT-coated AgNPs at 24 h has overlap in gene expression (n = 312 coordinately regulated DEGs; one discordantly regulated ( Figure 2C, circle)), as well as very distinct differences (n = 477 unique DEGs (bPEI) and n = 285 unique DEGs (CIT)). These figures are exemplars, but all contrasts and genes with annotation can be explored in our accompanying Rshiny application (https://www.niehs.nih.gov/research/resources/software/biostatistics/agnp/index.cfm).…”
mentioning
confidence: 99%
“…[34,35] While blood compatibility of AgNPs is unclear, [36] contradictory results are likely due to differences in AgNP surface chemistry [37] or due to differing protein corona compositions. [22,28] Finally, some studies report changes in metallothionein expression from AgNP exposure. [9,38] Despite differential expression of some metallothioneins in our analysis, we do not find global changes in expression of metallothioneins here (analysis available in the RShiny application).…”
mentioning
confidence: 99%
“…Whether or not the AgNPs toxicity is triggered by Ag + release or is nano‐specific, once AgNPs are internalized, they are immediately surrounded by biomolecules and then interact with these biomolecules that are mainly proteins . When the AgNPs and proteins interaction occurs in the cells, the AgNPs can alter protein conformation inducing unexpected biological reactions and lead to cytotoxicity . In CHO‐K1 cells, internalized AgNPs bound on sulfide groups and formed stable AgïŁżS bonds and then decreased the cell viability .…”
Section: Introductionmentioning
confidence: 99%
“…[25] When the AgNPs and proteins interaction occurs in the cells, the AgNPs can alter protein conformation inducing unexpected biological reactions and lead to cytotoxicity. [26,27] In CHO-K1 cells, internalized AgNPs bound on sulfide groups and formed stable AgS bonds and then decreased the cell viability. [22] Fourier transform infrared spectroscopy showed that both AgNPs and Ag + can be complexed with thiol groups and are able to induce protein misfolding in treated E. coli.…”
Section: Introductionmentioning
confidence: 99%